Convective heat transfer performance of airfoil heat sinks fabricated by selective laser melting - Ho, Jin Yao (2017)
This paper presents the forced convective heat transfer performances of novel airfoil heat sinks produced by Selective Laser Melting (SLM). Heat sinks with staggered arrays of NACA 0024 and NACA 4424 airfoil shaped fins were investigated experimentally and the results were compared with conventional heat sinks with circular and rounded rectangular fins. In addition, NACA 0024 heat sinks with angles of attack (α) ranging from 0° to 20° were also fabricated and the effects of the angle of attack (α) on the heat sink thermal performances were examined. Experiments were conducted in a rectangular air flow channel with tip (CLt) and lateral (CLh) clearance ratios of 2.0 and 1.55 and with Reynolds numbers (Re) ranging from 3400 to 24,000. Numerical studies were first performed to validate the experimental results of the circular finned heat sink and reasonably good agreement between the experimental data and numerical results were observed. Comparison of the experimental results showed that the heat transfer performances of the airfoil and rounded rectangular heat sinks exceeded those of the circular heat sink. The experimental Nusselt numbers were computed based on the heat sink base area (Nub) and the total heat transfer area (Nut). In comparison with the circular heat sink, highest enhancements in Nub and Nut of the NACA 0024 heat sink at α = 0° were 29% and 34.8%, respectively. In addition, the overall heat transfer performances of the NACA 0024 heat sinks were also seen to increase with increasing α. The results suggest that the streamline geometry of the airfoil heat sink has low air flow resistance, which resulted in insignificant bypass effect and thereby improving the heat sink thermal performance. In addition, the increase in α further improves the heat transfer performance of the NACA 0024 heat sinks through the formation of vortices which enhanced fluid mixing. Finally, based on the above mechanisms proposed, a semi-analytical model was developed to characterize the heat transfer performances of the NACA 0024 heat sinks for the range of α and Re tested. In comparison with the experimental data, reasonably accurate predictions were achieved with the model where the deviations in Nub were less than 7% for Re ≥ 6800.